Mitochondrial DNA in atherosclerosis research progress: a mini review - Liu, Zheng; Huang, Nan; Liu, Chan; Wu, Can; Zhou, Ling; Liu, Xiang; Lei, Haibo (Frontiers in Immunology, 2025)
Atherosclerosis (AS) is a chronic inflammatory disease that primarily affects large and medium-sized arteries and is one of the leading causes of death worldwide. This article reviews the multifaceted role of mitochondrial DNA (mtDNA) in AS, including its structure, function, release, and relationship with inflammation. Damage and release of mtDNA are considered central drivers in the development of AS, as they participate in the progression of AS by activating inflammatory pathways and affecting lipid metabolism. Therefore, therapeutic strategies targeting mtDNA and its downstream effects may provide new avenues to address this global health challenge.